Mind-Wandering and Meta-Awareness A Conversation with Jonathan Schooler. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Jonathan Schooler, Professor of Psychological and Brain Sciences at the University of California, Santa Barbara. This wide-ranging conversation examines how mind-wandering can serve as a window into the psychological world of meta-awareness. further topics include the nature of consciousness, mindfulness, creativity, free will, verbal overshadowing and more. This carefully-edited book includes an introduction, Back to the Future, and questions for discussion at the end of each chapter. Howard Burton was the Foundin.